A synthetic cytokinin primes photosynthetic and growth response in grapevine under ion-independent salinity stress. Issue 1 (31st December 2022) - Montanaro, Giuseppe; Briglia, Nunzio; Lopez, Loredana; Amato, Davide; Panara, Francesco; Petrozza, Angelo; Cellini, Francesco; Nuzzo, Vitale
ABSTRACT: Aiding optimal plant–environment interaction would favor plant resilience against environmental constrains including salt stress. We test the hypothesis that 6-Benzylaminopurine (BAP) primes grapevine's salt tolerance in vines ( Vitis vinifera ) received salt water (NaCl 100 mM) through the modulation of gene expression of BAP ( AHK4, AHP1 ) and salt-stress ( CAT, APX ) inducible genes and morpho-physiological traits. A subgroup of vines had previously (48 h) been primed with BAP (80 mg/L) before salt stress. The gene expressions were 30% ( CAT ) and 56% ( APX ) lower in primed salt-stressed vines than that in un-primed. Salt treatment did not increase leaf Na + but it lowered stomatal conductance ( g s ), photosynthesis (A), stem water potential (less negative) and photosystem-II efficiency ( F v / F m ). Chlorophyll- a concentrations were 30% higher in BAP-primed compared to un-primed. Adverse effects of salt were significantly reduced, maintaining high A/ g s, F v / F m and growth. After the relief of the stress, the BAP primed vines had a fast recovery.